Meckel's diverticulum as a cause of mechanical intestinal obstruction in an adult. A case report - Indira Noa Lores; Yodanky Ochoa Rodríguez; Yolexi Laborí Columbié (Medisur)
Meckel's diverticulum is diagnosed by a complication. There are three most common complications: hemorrhage, inflammation, and occlusion. The last one occurs more frequently in children. It has a higher incidence in males, however, in recent years in the Baracoa municipality (Guantánamo, Cuba) there have been several cases, five in 2019 and one in 2020; four of them were women. The clinical case of a 62-years-old patient is presented, with a history of abdominal surgery due to perforated duodenal ulcer, which required medical attention in the Surgery on-call service, of the Baracoa municipal hospital, due to colic-type abdominal pain, vomiting and difficulty in expelling stool and gas. She was hospitalized with a presumptive diagnosis of mechanical intestinal occlusion due to post-surgical bands and an exploratory laparotomy was performed, with a diagnostic finding of an inflamed Meckel's diverticulum. It was concluded with intestinal resection of the ileum segment. The patient evolved satisfactorily and was discharged on the eighth day after the intervention, without complications.